Porcine epidemic diarrhea virus (PEDV): An update on etiology, transmission, pathogenesis, and prevention and control - Jung, Kwonil; Saif, Linda J.; Wang, Qiuhong (Virus research, 2020)
•Porcine epidemic diarrhea virus (PEDV) causes acute diarrhea, dehydration and high mortality in neonatal pig.•S INDEL and non-S INDEL strains were detected during the diarrheal disease outbreak in US swine in 2013–2014.•The non-S INDEL PEDV was highly virulent, whereas the S INDEL PEDV caused milder disease.•The main PEDV transmission route is fecal–oral, but airborne transmission via the fecal–nasal route may also occur.•PEDV-specific IgA effector and memory B cells in orally primed sows play a critical role in sow lactogenic immunity. Porcine epidemic diarrhea virus (PEDV), a member of the genus Alphacoronavirus in the family Coronaviridae, causes acute diarrhea and/or vomiting, dehydration and high mortality in neonatal piglets. Two different genogroups of PEDV, S INDEL [PEDV variant containing multiple deletions and insertions in the S1 subunit of the spike (S) protein, G1b] and non-S INDEL (G2b) strains were detected during the diarrheal disease outbreak in US swine in 2013–2014. Similar viruses are also circulating globally. Continuous improvement and update of biosecurity and vaccine strains and protocols are still needed to control and prevent PEDV infections worldwide. Although the non-S INDEL PEDV was highly virulent and the S INDEL PEDV caused milder disease, the latter has the capacity to cause illness in a high number of piglets on farms with low biosecurity and herd immunity. The main PEDV transmission route is fecal–oral, but airborne transmission via the fecal–nasal route may play a role in pig-to-pig and farm-to-farm spread. PEDV infection of neonatal pigs causes fecal virus shedding (alongside frequent detection of PEDV RNA in the nasal cavity), acute viremia, severe atrophic enteritis (mainly jejunum and ileum), and increased pro-inflammatory and innate immune responses. PEDV-specific IgA effector and memory B cells in orally primed sows play a critical role in sow lactogenic immunity and passive protection of piglets. This review focuses on the etiology, transmission, pathogenesis, and prevention and control of PEDV infection.